2019
DOI: 10.1002/lsm.23200
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Pulsed Nd:YAG (1,064 nm) Laser Versus Q‐Switched Nd:YAG (1,064 nm) Laser for Treatment of Onychomycosis

Abstract: Background and ObjectivesTo compare the efficacy of the long‐pulsed Nd:YAG (1,064 nm) laser versus the Q‐Switched Nd:YAG (1,064 nm) laser in treatment of onychomycosis.Study Design/Materials and MethodsThis is a prospective cohort study. It was carried out on 20 patients with clinical and mycological evidence of onychomycosis who were randomly assigned into two groups; group I: included 10 patients treated with biweekly sessions of long‐pulsed Nd:YAG (1064 nm) laser and group II; included 10 patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
4
4
1
Order By: Relevance
“…Such results were also in agreement with Elmorsy et al, who concluded in their studies that both Q‐Switched Nd:YAG (1064 nm) and long‐ pulsed Nd:YAG (1064 nm) lasers are effective and safe modalities in the treatment of onychomycosis, especially in patients who have a contraindication to the use of oral antifungals 19 …”
Section: Discussionsupporting
confidence: 90%
“…Such results were also in agreement with Elmorsy et al, who concluded in their studies that both Q‐Switched Nd:YAG (1064 nm) and long‐ pulsed Nd:YAG (1064 nm) lasers are effective and safe modalities in the treatment of onychomycosis, especially in patients who have a contraindication to the use of oral antifungals 19 …”
Section: Discussionsupporting
confidence: 90%
“…The efficiency of such treatment is limited since the nail plate is an effective barrier for the delivery of local pharmaceuticals to the nail bed affected by the fungus [4,5]. Laser radiation can also be used for the treatment of onychomycosis [6‐9].…”
Section: Introductionmentioning
confidence: 99%
“…It has the advantage of being able to treat deep fungal infections. In recent years, the Nd:YAG laser has mostly been used to treat onychomycoses ( 9 ), Candida albicans ( 10 ), chromomycosis ( 11 ), warts ( 12 ), and some vascular and pigmentary diseases ( 13 ). In our early clinical study, we found that utilizing the Nd:YAG 1,064-nm laser as an additional treatment shortened the duration of sporotrichosis therapy, reduced the amount of azole antifungal drugs used, and decreased drug resistance.…”
Section: Introductionmentioning
confidence: 99%